История генуэзских владений в Крыму в трудах медиевистов Украины (30—первая половина 80-х гг. XIX в.) - Лиман, С.И. (My University, 2009)
Лиман С. І. Історія генуезьких володінь в Криму в працях медієвістів України (30-ті—перша половина 80-х рр. XIX ст.) У статті розглядається історія вивчення медієвістами України в 30-х—першій половині 80-х рр. XIX ст. різних проблем середньовічних генуезьких колоній в Криму і впливу на долю цих колоній татар і турків-османів. Установлено, що дослідницька робота велася по декількох напрямках (історія, археологія, джерелознавство, епіграфіка, нумізматика). Головним центром вказаних досліджень була Одеса (з 1839 р. — Одеське товариство історії і стародавностей; з 1865 р. — Новоросійський університет). Головну увагу вчені приділяли історії Кафи, що було пов’язано з її провідною роллю серед усіх генуезьких поселень в Криму. Найбільший внесок у вивчення середньовічного минулого цих поселень зробили П. І. Кеппен, М. Н. Мурзакевич, В. Н. Юргевич, Ф. К. Брун. S. Liman. History оf Genovese Colonies in Crimea in the Works of Ukrainian Medievists (1830s—first half of 1880s) The article discusses the history of study by Ukrainian medievists in 1830s — first half of 1880s of various problems of medieval Genovese colonies in Crimea and the influence of Tartars and Osmanic Turks on the fate of those colonies. This work is found to have been performed in several aspects (history, archaeology, source studies, epigraphics and numismatics). These studies met the level of their contemporary science, many of their findings preserving scientific value up to our days. The main center of such studies was Odessa (Odessa Society of History and Antiquities since 1839, University of Novorossia since 1865). Further expansion of their themes is tracked. The scientists paid attention mostly to history of Caffa, due to its leading position among all Genovese settlements in Crimea. The largest contribution to the study of medieval past of those settlements was brought by Pp. I. Keppen, N. N. Murzakevich, V. N. Yurgevich, F. K. Brun.
Keywords: Генуезькі; середньовічні; медієвісти; історіографія; Крим; Genovese; medieval; medievists; historiography; Crimea